Efficacy of tocilizumab in Takayasu arteritis: Multicenter retrospective study of 46 patients. (July 2018) - Mekinian, Arsene; Resche-Rigon, Mathieu; Comarmond, Cloé; Soriano, Alessandra; Constans, Joel; Alric, Laurent; Jego, Patrick; Busato, Florian; Cabon, Matthieu; Dhote, Robin; Estibaliz, Lazaro; Pault, Isabelle Kone; et al.
Abstract: Objectives: To assess the efficacy of tocilizumab in patients with Takayasu arteritis (TA). Methods: We conducted a retrospective multicenter study in 46 TA patients treated with tocilizumab. We analyzed factors associated with response to tocilizumab (assessed using NIH score). Results: Forty-six patients with TA were included, with a median age of 43 years [29–54], and 35 (76%) females. We observed a decrease in the median NIH scale (from 3 [2–3] at baseline to 0 [0–1] and 0 at 3 and 6 months, respectively; p < 0.0001). The daily prednisone dose also decreased from 15 mg [8–19] at baseline to 4 mg [5–21] and 5 mg [4.5–9] at 3 and 6 months, respectively (p < 0.0001) under tocilizumab. The overall tocilizumab failure free survival was 81% [CI 95%; 0.7–0.95], 72% [CI 95%; 0.55–0.95] and 48% [CI 95%; 0.2–0.1] at 12, 24 and 48 months, respectively. The presence of constitutional symptoms (HR 5.6 [CI 95%; 1.08–29], p = 0.041), and C-reactive protein level (HR 1.16 [CI 95%; 1.01–1.31], P = 0.003) at the time of tocilizumab initiation were significantly associated with tocilizumab event-free survival. The event-free survival was significantly better under tocilizumab therapy in comparison to DMARDs (p = 0.02). Conclusion: This large multicenter study shows that tocilizumab is efficient and may reduce the incidence of relapses in TA. Highlights: Tocilizumab can lead patients TA to remission in 80%, have steroid sparing effect and a good safety profile. Tocilizumab can be used in monotherapy and as first line therapy. Tocilizumab can be used in monotherapy and is effective as first line therapy.